Kajian Yuridis Kebijakan Hukum Pidana dalam Penerapan Asesemen Terpadu bagi Penyalah Guna Narkoba berdasarkan Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika - Muslim, Daud; Darwis, Nurlely; Sudarto, Sudarto (Neolectura, 2024)
Drug crimes pose a serious threat with detrimental effects on the global community, including Indonesia. Drugs are classified as extraordinary crimes that harm physical, mental, social, and economic health. Drug abusers are not criminals who should be imprisoned but individuals who need medical and social rehabilitation, as regulated in Law Number 35 of 2009 on Narcotics. However, the implementation of rehabilitation faces challenges, such as a lack of synchronization among law enforcement agencies and the low number of abusers receiving rehabilitation. This study uses normative juridical research methods with a statute approach, conceptual approach, and case approach. Secondary data were obtained from legal literature and relevant regulations. The results of the study show that the integrated assessment mechanism, involving both medical and legal evaluations, plays a crucial role in determining whether drug abusers are eligible for rehabilitation or imprisonment. However, various obstacles hinder its implementation, such as differing legal interpretations, sectoral egos among institutions, and inconsistencies in placing drug abusers in rehabilitation centers. Moreover, the criminal law policy that prioritizes rehabilitation as a solution requires reform to be more effective in preventing drug-related crimes. The study recommends improving coordination among law enforcement agencies and revising regulations to ensure rehabilitation is prioritized in handling drug abuse cases, aiming to create a more humane and effective justice system.